Achieving sustainable economic growth in Sub-Saharan African countries using the tool of monetary policy effectiveness - Areghan Isibor; Alex Omankhanlen; Benjamin Ehikioya; Godswill Osuma; Adenike Oladipo; Adedoyin Bunmi-Alo; Kikiyanu Ajalaadebowale (Journal of Central Banking Theory and Practice, 2023)
The issue of achieving and sustaining a nation's economicgrowth is an issue that is of concern to many nations of the world,especially the sub-Saharan African (SSA) nations. This was in linewith the United Nations Sustainable Development Goal (SDG) 8 ofEconomic Growth. This study, therefore, examines how monetarypolicy tools can help the SSA governments achieve the SDG 8 goaland also sustain it. Relevant secondary data on sustained economicgrowth (GDPPC) (dependent variable) and interest rate, exchangerate, money supply, and inflation rate (independent variable) weregathered from the annual report of the Central Banks of the 48 SSAnations. The panel data year covers the period from 2016 to 2022.The unit root test confirms the variables to have a level integrationorder. The Hausman test suggests the use of fixed effect regression.The fixed effect regression shows that for the 48 SSA nations, interestrate, inflation rate, and money supply were positively significant inimpacting GDPPC while exchange rate was negatively significant inimpacting GDPPC. The study, therefore, recommends that importpromotion, for example, should be avoided because it raises the ex-change rate and lowers the value of currencies of the SSA nations.
Keywords: E52; E58; O10; 330; Sustainable Development Goal; Sub-Saharan Africa; Sustainable Economic Growth; Inflation; GDP Per Capita; ExchangeRate